2010
DOI: 10.1073/pnas.0907531107
|View full text |Cite
|
Sign up to set email alerts
|

Glacier and landslide feedbacks to topographic relief in the Himalayan syntaxes

Abstract: Despite longstanding research on the age and formation of the Tibetan Plateau, the controls on the erosional decay of its margins remain controversial. Pronounced aridity and highly localized rock uplift have traditionally been viewed as limits to the dissection of the plateau by bedrock rivers. Recently, however, glacier dynamics and landsliding have been argued to retard headward fluvial erosion into the plateau interior by forming dams and protective alluvial fill. Here, we report a conspicuous clustering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(99 citation statements)
references
References 30 publications
2
97
0
Order By: Relevance
“…In the literature, many single landslide dam study cases have been reported (e.g., King et al 1989;Hermanns et al 2004;Dai et al 2005;Nash et al 2008;Duman 2009;Degraff et al 2010;Evans 2015, 2017;Emmer and Kalvoda 2017). Several landslide dam inventories have been collected in different parts of the world, such as in North America (O'Connor and Costa 1993), South America (Hermanns et al 2011), Europe (Casagli and Ermini 1999;Bonnard 2011;Tacconi Stefanelli et al 2015), Central Asia (Popov 1990;Hewitt 1998;Strom 2010;Korup et al 2010;Schneider et al 2013), China (Dong et al 2009;Fan et al 2012;Peng and Zhang 2012), and New Zealand (Korup 2004). Although some reports on single events in the Cordillera Blanca Mountain Range, Peru, have been researched (Lliboutry et al 1977;Zapata 2002;Carey 2005;Hubbard et al 2005), no landslide dams and related lakes archive or any extended study on these topics are available yet.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, many single landslide dam study cases have been reported (e.g., King et al 1989;Hermanns et al 2004;Dai et al 2005;Nash et al 2008;Duman 2009;Degraff et al 2010;Evans 2015, 2017;Emmer and Kalvoda 2017). Several landslide dam inventories have been collected in different parts of the world, such as in North America (O'Connor and Costa 1993), South America (Hermanns et al 2011), Europe (Casagli and Ermini 1999;Bonnard 2011;Tacconi Stefanelli et al 2015), Central Asia (Popov 1990;Hewitt 1998;Strom 2010;Korup et al 2010;Schneider et al 2013), China (Dong et al 2009;Fan et al 2012;Peng and Zhang 2012), and New Zealand (Korup 2004). Although some reports on single events in the Cordillera Blanca Mountain Range, Peru, have been researched (Lliboutry et al 1977;Zapata 2002;Carey 2005;Hubbard et al 2005), no landslide dams and related lakes archive or any extended study on these topics are available yet.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the upper Indus River Basin is bereft of any meaningful technical data because the region is inaccessible due to the severe terrain conditions, the absence of LiDAR imagery, lack of high quality aerial photography, and paucity of local expertise with respect to the identification of landslide-related geomorphic features. The results obtained from this study were validated with landslide inventory mapping [Ahmed and Rogers, 2014] as well as historic data obtained from more than 350 documented rockslides [Hewitt, 1982[Hewitt, , 1998Shroder, 1993;Shroder and Bishop, 1998;Korup et al, 2010;Hewitt et al, 2011], scattered throughout the Upper Indus watershed. The major objective of this study was to prepare a regional reconnaissance landslide susceptibility map of the upper Indus River Basin which can play a key role in identifying those areas where more detailed landslide hazard mapping might, or should be, undertaken in the future.…”
Section: Introductionmentioning
confidence: 82%
“…The main Indus River channel originates in the Tibetan Plateau, one of the planet's greatest active erosional platforms [Korup et al, 2010]. The Indus River drainage system encompasses a very large catchment area and its tributaries tend to follow the longitudinal valleys in the steepest areas, then flow anomalously, cutting across the structural grain of the mountains until they join the main stem of the Indus River in northern Pakistan [Kazmi and Jan, 1997;Leland et al, 1998].…”
Section: Study Areamentioning
confidence: 99%
“…The greater the circulation a wing creates, the higher the lift it produces. At each wing tip, however, the circulation around the wing rolls up into a tip vortex, which extends backward like a tube, and that deposition in response to landslides can protect river beds from eroding over millennial timescales 10 , it is unclear what physical processes drive hiatuses in incision over timescales of 1 million to 10 million years. Such long timescales span multiple glacial-interglacial climate cycles, and may also reflect a connection to deep Earth processes.…”
Section: News and Views F L O R I A N T M U I J R E S And M I C H A E L mentioning
confidence: 99%